(untitled) (Bangladesh Journal of Medical Biochemistry, 2013)
Polycystic Ovary Syndrome (PCOS) was originally described as a syndrome of amenorrhea, hirsutism and obesity associated with enlarged polycystic ovaries. There is increased androgen level and in some, insulin resistance (IR). Etiological relationship of androgen excess and IR in PCOS is not established. Influence of obesity on PCOS is controversial. This study was designed to see the androgen and insulin status in PCOS among obese and non-obese patients. It was a case-control study. Of total 80 study subjects, 60 primary infertile women suffering from PCOS were cases (30 obese and 30 non-obese). Age and BMI matched 20 healthy women having normal menstrual cycles were controls (10 obese and 10 non-obese). Age range of all were 20-40 years. Fasting plasma glucose, fasting S. Insulin and free Testosterone were measured. Insulin resistance (IR) was assessed by fasting glucose to insulin ratio (<4.5). Subjects with DM or known endocrine disorders that may be associated with abnormal S.Insulin or plasma glucose concentration were excluded. No significant difference of fasting plasma glucose between PCOS (obese or non-obese) and respective controls (P>0.5, in each) were observed. Significant difference of fasting S. Insulin and testosterone were observed between PCOS (both obese and non-obese) and respective controls (P<0.01 in each), but there was no significant difference between obese and non-obese PCOS (P>0.05). There was no significant difference of S.Testosterone between obese and non-obese PCOS(P>0.05). There was also no significant difference of IR between obese and non-obese PCOS, but the ratio was <4.5 (indicating IR in both). There were no significant correlation of S.Insulin with Testosterone in any group of PCOS (obese and non-obese) (P>0.05). Increased S.Insulin and Testosterone was seen in PCOS irrespective of BMI. Further studies with larger sample size is recommended to assess etiological relationship between insulin and testosterone in PCOS. DOI: http://dx.doi.org/10.3329/bjmb.v3i1.13801 Bangladesh J Med Biochem 2010; 3(1): 11-15